2016
DOI: 10.1530/joe-16-0324
|View full text |Cite
|
Sign up to set email alerts
|

The role of the p53 tumor suppressor in metabolism and diabetes

Abstract: In the context of tumor suppression, p53 is an undisputedly critical protein. Functioning primarily as a transcription factor, p53 helps fend off the initiation and progression of tumors by inducing cell cycle arrest, senescence or programmed cell death (apoptosis) in cells at the earliest stages of precancerous development. Compelling evidence, however, suggests that p53 is involved in other aspects of human physiology, including metabolism. Indeed, recent studies suggest that p53 plays a significant role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 134 publications
(140 reference statements)
3
104
1
3
Order By: Relevance
“…The reappearance of beige adipocytes in WATs conceivably contributed to the improved insulin sensitivity in aged Adipoq-p53iKO mice. However, it is also possible that p53 ablation ameliorates insulin resistance via pathways independent of beige adipocyte formation (58,59). From the perspective of energy homeostasis, the restoration of WAT beiging represents an attractive strategy of clinical significance, in that the augmentation of EE and amelioration of white adipocyte hypertrophy, as observed in this study, may eliminate a rudimentary cause of WAT insulin resistance.…”
Section: Discussionmentioning
confidence: 75%
“…The reappearance of beige adipocytes in WATs conceivably contributed to the improved insulin sensitivity in aged Adipoq-p53iKO mice. However, it is also possible that p53 ablation ameliorates insulin resistance via pathways independent of beige adipocyte formation (58,59). From the perspective of energy homeostasis, the restoration of WAT beiging represents an attractive strategy of clinical significance, in that the augmentation of EE and amelioration of white adipocyte hypertrophy, as observed in this study, may eliminate a rudimentary cause of WAT insulin resistance.…”
Section: Discussionmentioning
confidence: 75%
“…In an old study from 1979, they found that patients with diabetes have two to four times greater risk of developing coronary heart disease (Kannel and McGee, 1979). A literature review by Kung and Murphy (2016) on the role of p53 in metabolism, pancreatic function, glucose homeostasis and insulin resistance showed that p53 is a key player in diabetes and in the severity of diabetic phenotypes. A study conducted on a Russian population concluded that the codon 72 polymorphism of the p53 gene is associated with type 1 diabetes (Spitsina et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The p53 gene encodes the synthesis of a nuclear phosphoprotein of 53 kDa, where the name p53 comes from, and the protein has 393 amino acids. The functionally active (wild-type) form of p53 has a tetrameric molecular structure (Kung and Murphy, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…2B-E). p53 is also implicated in the development of insulin resistance and diabetes (75). Kyoto Encyclopedia of Genes and Genomes (KEGG; https:// www.genome.jp/kegg/kegg1.html) analysis of the transcriptome of diabetic and nondiabetic mice indicated, in fact, that significant differentially expressed genes closely associate with the p53 signaling network as well as the MAPK and TGF-b pathways (76).…”
Section: Involvement Of P53 In Renal Diseasementioning
confidence: 99%